Hindu Pluralism: Religion and the Public Sphere in Early Modern South India - Fisher, Elaine M. (South Asia Across the Disciplines, 2017)
Frontmatter -- Contents -- Acknowledgments -- Introduction -- 1. Hindu Sectarianism: Difference in Unity -- 2. "Just Like Kālidāsa": The Making of the Smārta-Śaiva Community of South India -- 3. Public Philology: Constructing Sectarian Identities in Early Modern South India -- 4. The Language Games of Śiva: Mapping Text and Space in Public Religious Culture -- Conclusion: A Prehistory of Hindu Pluralism -- Appendix -- Notes -- Bibliography -- Index